2020
DOI: 10.1016/j.ssci.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the bottleneck flow between preschool children and adults under different movement motivations

Abstract: Highlights  We analyze bottleneck flow of preschool children in a laboratory experiment.  The pedestrian flow of children and adult under different movement motivations are compared.  The relation between flow and bottleneck width for children and adults are unified.  Arch-like and teardrop-shape distribution are observed for the children' and adults' movement respectively. Abstract:Understanding on children's movement characteristics is significant to improve their safety levels especially under emergenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 36 publications
2
25
1
Order By: Relevance
“…It is observed that the distributions of density are inhomogeneous over space and we observe the gradual change from high density to low density. Similar to the previous study of children passing through the bottleneck 4 , the congested areas in front of the exit display an arch-like shape, and the shape of the peak density region is similar to ellipses, whereas the peak density reaches about 7 ped/m 2 in this study which is a bit smaller than the value 8 ped/m 2 in the previous study 4 . Moreover, the peak density locates in the middle of the exit, which is closer to the bottleneck entrance compared to the previous study 4 .…”
Section: Experimental Profilessupporting
confidence: 85%
See 2 more Smart Citations
“…It is observed that the distributions of density are inhomogeneous over space and we observe the gradual change from high density to low density. Similar to the previous study of children passing through the bottleneck 4 , the congested areas in front of the exit display an arch-like shape, and the shape of the peak density region is similar to ellipses, whereas the peak density reaches about 7 ped/m 2 in this study which is a bit smaller than the value 8 ped/m 2 in the previous study 4 . Moreover, the peak density locates in the middle of the exit, which is closer to the bottleneck entrance compared to the previous study 4 .…”
Section: Experimental Profilessupporting
confidence: 85%
“…Previous studies propose that higher competition leads to longer time headway both for children and for adults 4,24 . However, there exists a great difference in movement motivation of previous researches 4,24 , which doubts us the difference of time gap between children and adults both in similar high motivation. Considering this, we aim to study the distribution of the time gap of highly motivated children and adults.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The evacuation experiment was semi-announced [3,11,12]; that is to say, the teachers knew about it, but the children did not. In order to ensure that the children participating in the experiment did not know what was ahead, the teachers told them they were going to play games when we installed the sensors on the children.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the study of the evacuation of children has attracted the attention of researchers. Some countries have collected some data on the evacuation of children, mainly focusing on children's speed of movement (horizontal or by stairs), flow-density relationships, (pre)evacuation time and their route selection [2,3,5,[9][10][11][12][13]. How to evaluate children's own perception of risk has not been covered in previous studies, leading to slow progress in research on children's evacuation behaviour and subsequent development of simulation models.…”
Section: Evacuation Behavioursmentioning
confidence: 99%